Social contract vs. invisible hand: Agreeing to solve social dilemmas - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2016)
[Introduction ...] The purpose of this essay is to take a closer look at the relation between the invisible hand paradigm that is at the heart of economists' theoretical outlook at markets and the social contract paradigm. In support of the above-quoted claim that the contractarian paradigm can “provide us with the `bridge' between the individual-choice calculus and group decisions,” I shall seek to show that this paradigm, with its individualistic approach to organized collective action, provides indeed the fitting complement to the invisible hand paradigm as a theory of spontaneous social order, paradigmatically exemplified by the order of the market. The paper is organized as follows. Section 2 looks at the principal tenets of the social contract tradition. Section 3 reviews the 18th century origins of the “invisible hand” paradigm as the theoretical core of the economics tradition. Section 4 examines the limits of invisible hand accounts, specifically with regard to the problems posed by social dilemmas. Section 5 deals with the modern revival of social contract theory. Section 6 looks specifically at the contractarian constitutionalism of James Buchanan, the economist among the “new contractarians.” The concluding section relates the contrast between the invisible hand paradigm and social contract theory to the distinction between the “two kinds of order,” spontaneous orders and corporate orders, that plays a central role in F.A. Hayek's work.
Keywords: 330